2023
DOI: 10.3389/fpubh.2023.1166106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on community-based brain injury associations across Canada: a cross-sectional survey study

Ana Paula Salazar,
Carolina Bottari,
Sophie Lecours
et al.

Abstract: BackgroundThe COVID-19 pandemic created new difficulties for people living with brain injury, their families, and caregivers while amplifying the challenges of community-based associations that support them. We aimed to understand the effects of the pandemic on clients who live with brain injury, as well as on the provision of community brain injury services/programs in Canada.MethodsOnline cross-sectional survey conducted in January 2022. Representatives of brain injury associations across Canada completed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…8,15 A survey study of 45 key representatives from brain injury associations across Canada echoes these findings with participants noting that social isolation, loneliness, boredom, anxiety, and depression were frequent psychosocial challenges experienced by people living with brain injury during the COVID-19 pandemic. 16 This vulnerable population also experienced increased challenges related to personal finances, social support, and daily living during the pandemic. 4,5 Indeed, our results show that clients' specific needs related to basic finances, food, and housing increased during the first year of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,15 A survey study of 45 key representatives from brain injury associations across Canada echoes these findings with participants noting that social isolation, loneliness, boredom, anxiety, and depression were frequent psychosocial challenges experienced by people living with brain injury during the COVID-19 pandemic. 16 This vulnerable population also experienced increased challenges related to personal finances, social support, and daily living during the pandemic. 4,5 Indeed, our results show that clients' specific needs related to basic finances, food, and housing increased during the first year of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A 2022 pan-Canadian survey showed that, even though brain injury associations encountered financial difficulties, they quickly transitioned their support programs to online delivery and developed new programs to continue providing services to clients, while complying with protective measures. 16 Brain injury associations are part of the Canadian non-profit sector, which has also faced considerable challenges and many continue to report being in a precarious situation, often due to revenue declines and increased demand surpassing capacity. 17 Despite knowing that the pandemic has challenged brain injury associations, 16 little is known about the extent and type of changes that were undertaken by community associations in response to the pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation